2007
DOI: 10.1074/jbc.m701235200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Endoperoxide H Synthases

Abstract: The cyclooxygenase (COX) activity of prostaglandin endoperoxide H synthases (PGHSs) converts arachidonic acid and O 2 to prostaglandin G 2 (PGG 2 ). PGHS peroxidase (POX) activity reduces PGG 2 to PGH 2 . The first step in POX catalysis is formation of an oxyferryl heme radical cation (Compound I), which undergoes intramolecular electron transfer forming Intermediate II having an oxyferryl heme and a Tyr-385 radical required for COX catalysis. PGHS POX catalyzes heterolytic cleavage of primary and secondary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 74 publications
1
33
0
Order By: Relevance
“…An examination of huPGHS-2 heterodimers having a defective POX active site indicated that the COX site of a monomer cannot function unless the POX site of that monomer is functional (25). This finding implies that the monomer of native huPGHS-2 to which heme is bound is the COX catalytic monomer.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…An examination of huPGHS-2 heterodimers having a defective POX active site indicated that the COX site of a monomer cannot function unless the POX site of that monomer is functional (25). This finding implies that the monomer of native huPGHS-2 to which heme is bound is the COX catalytic monomer.…”
Section: Discussionmentioning
confidence: 87%
“…Expression, Purification, and Assay of huPGHS-2-Procedures for the expression of huPGHS-2 in insect cells and purification of the enzyme were essentially the same as those reported previously (17,24,25). The purity of the recombinant huPGHS-2 was determined by SDS-PAGE and by Western blot analysis (24).…”
Section: Methodsmentioning
confidence: 99%
“…Val-291 is one of these residues, which form a dome over the distal heme side of COX-1. The V291A mutant retained cyclooxygenase and peroxidase activities (27). 5,8-and 7,8-LDS also have valine residues in the homologous position, whereas 8,11-LDS and 10R-DOX have leucine residues (Fig.…”
Section: 8-lds Of G Graminis and Magnaporthe Grisea And 58-lds Ofmentioning
confidence: 99%
“…PGG 2 and presumably 8R-HPODE bind to the distal side of the heme group, which can be delineated by hydrophobic amino acid residues (27). Val-291 is one of these residues, which form a dome over the distal heme side of COX-1.…”
Section: 8-lds Of G Graminis and Magnaporthe Grisea And 58-lds Ofmentioning
confidence: 99%
See 1 more Smart Citation